Immunodominant IgM and IgG Epitopes recognized by antibodies induced in enterovirus A71-Associated hand, foot and mouth disease patients - Aw-Yong, K.L.; Sam, I.C.; Koh, M.T.; Chan, Y.F. (Public Library of Science, 2016)
Enterovirus A71 (EV-A71) is one of the main causative agents of hand, foot and mouth disease (HFMD). Unlike other enteroviruses that cause HFMD, EV-A71 is more frequently associated with severe neurological complications and fatality. To date, no effective licensed antivirals are available to combat EV-A71 infection. Little is known about the immunogenicity of viral non-structural proteins in humans. Previous studies have mainly focused on characterization of epitopes of EV-A71 structural proteins by using immunized animal antisera. In this study, we have characterized human antibody responses against the structural and non-structural proteins of EV-A71. Each viral protein was cloned and expressed in either bacterial or mammalian systems, and tested with antisera by western blot. Results revealed that all structural proteins (VP1-4), and non-structural proteins 2A, 3C and 3D were targets of EV-A71 IgM, whereas EV-A71 IgG recognized all the structural and non-structural proteins. Sixty three synthetic peptides predicted to be immunogenic in silico were synthesized and used for the characterization of EV-A71 linear B-cell epitopes. In total, we identified 22 IgM and four IgG dominant epitopes. Synthetic peptide PEP27, corresponding to residues 142-156 of VP1, was identified as the EV-A71 IgM-specific immunodominant epitope. PEP23, mapped to VP1 41-55, was recognized as the EV-A71 IgG cross-reactive immunodominant epitope. The structural protein VP1 is the major immunodominant site targeted by anti-EV-A71 IgM and IgG antibodies, but epitopes against non-structural proteins were also detected. These data provide new understanding of the immune response to EV-A71 infection, which benefits the development of diagnostic tools, potential therapeutics and subunit vaccine candidates.